Prevention of Cardiovascular Complications in Surgery of the Aorta and Its Branches - M. I. Neimark; O. A. Kirichuk; Ye. A. Klyzhina (Общая реаниматология)
Objective: to substantiate the possibilities of preventing cardiovascular complications during elective surgical treatment for atherosclerosis of the aorta and its branches, by blocking the sympathetic trunk via prolonged thoracic epidural anesthesia (TEA). Subjects and methods. A hundred and thirty-seven patients who had undergone iliofemoral bypass surgery were examined. According to the method of anesthesia, the patients were divided into 3 groups: 1) the patients in whom SA was used at the LII-LIII level; 2) those in whom surgery was performed under EA at the ThXII-LI level; 3) those in whom TEA was employed at the ThX-ThXI level. Results. The comparative study showed that in Group 3, cardiac index (CI) and stroke index (SI) were higher at all stages of surgery and in the postoperative period than those in Groups 1 and 2; in Group 3, specific peripheral vascular resistance decreased moderately and remained steady-state at all stages of the study. Group 3 patients were found to have the highest CI values, SI being greater than the baseline values with the use of TEA (ThX-ThXI). To elucidate the causes of this circumstance, the authors estimated the sympathetic activity in Groups 2 and 3 patients before and after surgery. Prior to surgery, in these groups it was increased by an average of 3.2 times as compared with the control values. After surgery under EA, in Group 2 patients the sympathetic activity decreased as compared with the baseline value, but exceeded the control value. In Group 3 patients, it reduced not only compared with the baseline value, but it was 1.6 times lower than the control value. Conclusion. TEA actually provides a partial sympathetic trunk blockage at the ThIV-ThX level, lowers the sympathetic activity, thus improving the indices of cardiac output. Key words: thoracic epidural anesthesia, atherosclerosis of the aorta and its branches, central hemodynamics, evoked skin autonomic potentials.